CD146 expression regulates osteochondrogenic differentiation of human adipose‐derived stem cells. Issue 1 (20th July 2021) - Scioli, Maria Giovanna; Storti, Gabriele; Bielli, Alessandra; Sanchez, Massimo; Scimeca, Manuel; Gimble, Jeffrey M.; Cervelli, Valerio; Orlandi, Augusto
Abstract: Tissue engineering aims to develop innovative approaches to repair tissue defects. The use of adipose‐derived stem cells (ASCs) in tissue regeneration was extensively investigated for osteochondrogenesis. Among the ASC population, ASCs expressing the CD146 were demonstrated to be multipotent and considered as perivascular stem cells, although the functional role of CD146 expression in these cells remains unclear. Herein, we investigated the influence of CD146 expression on osteochondrogenic differentiation of ASCs. Our results showed that, in two‐dimensional culture systems, sorted CD146 + ASCs proliferated less and displayed higher adipogenic and chondrogenic potential than CD146 − ASCs. The latter demonstrated a higher osteogenic capacity. Besides this, CD146 + ASCs in three‐dimensional Matrigel/endothelial growth medium (EGM) cultures showed the highest angiogenic capability. When cultured in three‐dimensional collagen scaffolds, CD146 + ASCs showed a spontaneous chondrogenic differentiation, further enhanced by the EGM medium's addition. Finally, CD146 − ASCs seeded on hexafluoroisopropanol silk scaffolds displayed a greater spontaneous osteogenetic capacity. Altogether, these findings demonstrated a functional and relevant influence of CD146 expression in ASC properties and osteochondrogenic commitment. Exploiting the combination of specific differentiation properties of ASC subpopulations and appropriate culture systems could represent a promising strategy to improve the efficacy of new regenerative therapies. Abstract : 1. Sorted adipose‐derived stem cell (ASC) subpopulations show distinct differentiation properties in two‐dimensional (2D) and 3D cultures. 2. CD146 +  ASCs cultured in collagen gel display the greatest chondrogenic ability. 3. CD146 −  ASCs cultured on the hexafluoroisopropanol scaffold show the highest osteogenic capacity. 4. The proper use of scaffolds and specific ASC subpopulations enhances osteochondrogenesis.